PENGARUH PROMOSI DAN HARGA TERHADAP MINAT BELI PRODUK MI INSTAN INDOMIE (VARIAN GORENG ORIGINAL) DI JAKARTA SELATAN - Sulistianto, R. Hario; Haikal, Fahri; Zahra, Putri Alifia; Fitri, Diin (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2025)
This study aims to determine whether promotion affects purchasing interest in Indomie products, to determine whether price has an impact on consumer purchasing interest in Indomie products, and to determine whether promotion and price simultaneously have an impact on purchasing interest in Indomie products. in the South Jakarta area. The sample in this study was Indomie product consumers with a total of 300 respondents., who lived in South Jakarta, and consumed fried Indomie products at least twice a month. This research used quantitative methods in the form of data collected from respondents' responses to questionnaires distributed via Google Forms. The results of this research show that promotions and prices have a significant influence on buying interest. This research also shows a simultaneous influence between promotion and price on buying interest in the original fried variant of the Indomie product in South Jakarta.